Analisis Faktor Risiko dan Penanganan Depresi Postpartum Pada Ibu Nifas: Literature Review - Rini Gustina Sari; Andriani Andriani; Reva Meise Sari (JOURNAL OF MIDWIFERY SCIENCE, 2025)
Postpartum depression is a mental health disorder experienced by approximately 10–20% of women after childbirth and can affect parenting quality, maternal health, and infant development. This condition is influenced by various interrelated factors, making comprehensive studies necessary. This study aimed to analyze the risk factors and management of postpartum depression based on previous research findings. The method used was a literature review of 10 relevant scientific articles. Articles were searched through Google Scholar and PubMed databases from publications between 2022 and 2026 using the keywords postpartum depression, social support, maternal mental health, postpartum women, and risk factors. The review findings indicated that socioeconomic factors and social support were the most dominant factors influencing the occurrence of postpartum depression. Age and educational level were identified as factors affecting maternal vulnerability. In addition, social stigma, lack of knowledge, and limited access to healthcare services were barriers to the management of postpartum depression. In conclusion, the management of postpartum depression requires improved education, strengthened social support, and optimized healthcare services to support maternal mental health after childbirth.